2016
DOI: 10.1292/jvms.15-0533
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant nucleocapsid protein-based indirect enzyme-linked immunosorbent assay to detect antibodies against porcine deltacoronavirus

Abstract: Recently, porcine deltacoronavirus (PDCoV) has been proven to be associated with enteric disease in piglets. Diagnostic tools for serological surveys of PDCoV remain in the developmental stage when compared with those for other porcine coronaviruses. In our study, an indirect enzyme-linked immunosorbent assay (ELISA) (rPDCoV-N-ELISA) was developed to detect antibodies against PDCoV using a histidine-tagged recombinant nucleocapsid (N) protein as an antigen. The rPDCoV-N-ELISA did not cross-react with antisera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…The detection results showed that 11% of samples were positive for antibodies against PDCoV. The total positive rate of the PDCoV antibodies in samples is similar to that reported in Heilongjiang province (11.6%) from January 2014 to June 2015 (Su et al, 2015). When compared with samples from farms with occurrence of diarrhea, the positive rate in Hebei province (11%) was much lower than that in Heilongjiang province (27.5%) (Su et al, 2015).…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…The detection results showed that 11% of samples were positive for antibodies against PDCoV. The total positive rate of the PDCoV antibodies in samples is similar to that reported in Heilongjiang province (11.6%) from January 2014 to June 2015 (Su et al, 2015). When compared with samples from farms with occurrence of diarrhea, the positive rate in Hebei province (11%) was much lower than that in Heilongjiang province (27.5%) (Su et al, 2015).…”
Section: Introductionsupporting
confidence: 70%
“…No crossreactivity was detected by virus neutralization, indirect immunofluorescence, and immunostaining assays using pig hyperimmune antisera to PEDV or PDCoV in that study (Ma et al, 2016) and the PEDV whole virus-based ELISA and the S1 protein-based ELISA showed no cross-reaction with pig antisera against PDCoV, PRCV or TGEV Purdue strain (Chen et al, 2016). While the S protein gene has a high degree of variability in the members of coronaviruses (Su et al, 2015), which could lead to decreased sensitivity, N protein gene is conserved, which could lead to cross-reaction to porcine coronaviruses (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…With increased concern about this newly emerging enteric disease, reverse-transcription polymerase chain reaction (RT-PCR), real-time RT-PCR, nested RT-PCR, and singleplex RT insulated isothermal PCR methods have been developed to detect PDCoV in clinical samples Wang et al, 2014a;Song et al, 2015;Zhang et al, 2015Zhang et al, , 2016. Enzyme-linked immunosorbent assays for PDCoV-specific serum antibodies, based on the PDCoV S1 or nucleocapsid protein, have also been used to determine the prevalence of anti-PDCoV immunoglobulin G (IgG) in pig serum (Su et al, 2015;Thachil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%